2002
DOI: 10.1672/0277-5212(2002)022[0528:gowagw]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of water and ground water in the Nhecolândia, Pantanal of Mato Grosso, Brazil: variability and associated processes

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
64
1
20

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 23 publications
6
64
1
20
Order By: Relevance
“…In October 2008, 19 lakes were sampled for hydrogeochemistry and 14 for limnological analyses, of which seven were EC < 750 μS.cm −1 and 12 EC > 2,000 μS.cm −1 . The results of the chemical analyses showed that all the waters were extremely poor in Ca 2+ and Mg 2+ but, in the salinas, rich in Na + and K + , as stated in the general literature (Zavarzin 2002) and that on Nhecolândia (Barbiero et al 2002. Table II presents the results of the August 2007 sampling, where the poverty in Ca 2+ and Mg 2+ ions is clear.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…In October 2008, 19 lakes were sampled for hydrogeochemistry and 14 for limnological analyses, of which seven were EC < 750 μS.cm −1 and 12 EC > 2,000 μS.cm −1 . The results of the chemical analyses showed that all the waters were extremely poor in Ca 2+ and Mg 2+ but, in the salinas, rich in Na + and K + , as stated in the general literature (Zavarzin 2002) and that on Nhecolândia (Barbiero et al 2002. Table II presents the results of the August 2007 sampling, where the poverty in Ca 2+ and Mg 2+ ions is clear.…”
Section: Resultssupporting
confidence: 59%
“…Such differences are essentially due to the greater isolation of the salinas from phreatic recharge by continuous horizons of greenish and grizzly soil of low porosity . Despite these different salinities, Barbiero et al (2002) and Furquim et al (2010) concluded that the salinas and baías waters belong to the same chemical family, excluding the possibility that the salinity is a legacy of past climatic periods. The isolation of the saline lakes is associated with high alkalinity, which helps to attack the quartzose sand and silt, supplying silica (in solution probably as H 3 SiO − 4 or H 2 SiO 2− 4 ) to precipitate Mg silicates (saponite and stevensite), illite and the amorphous silica cementing the grains of quartzose sand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, the salt has always been attributed to alternating humid and arid phases during the Pleistocene (i.e., inherited from the past), but Barbiéro et al (2002) have shown a unique geochemical family of waters evolving currently in an alkaline manner under the influence of evaporation [index word 3]. The geochemical composition changes gradually from feebly mineralised waters that flood the region during the rainy season to the strongly mineralised ones in the salinas.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it was shown that all the waters of this region belong to the same chemical family (Barbiero et al, 2002) and that the changes observed in the chemical composition (major elements) result from salt precipitation associated with the concentration process. Therefore, the saline lakes could arise from the present-day concentration of lowsalinity waters that supply the Pantanal area each year.…”
mentioning
confidence: 99%